2021
DOI: 10.3390/su13073991
|View full text |Cite
|
Sign up to set email alerts
|

Root Reinforcement Effect on Cover Slopes of Solid Waste Landfill in Soil Bioengineering

Abstract: This study investigated the effect of vegetation plant roots on the stability of the cover slopes of solid waste landfills. A large direct shear test and a root tensile strength test were conducted to quantify the effect of rooted soil of revegetation plants on the increment in shear strength of the soil as a method to protect the cover slope of solid waste landfills. In the large direct shear test, an increase in the shear strength of the ground with the presence of roots was observed, and the root reinforcem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Adding a root system can/significantly minimize the strainsoftening effect and concurrently increase soil shear strength metrics compared to the absence of a root system (Hallett, 2010;Pollen-Bankhead and Simon, 2010;Park et al, 2021;Su et al, 2021). The closer the sample is to the optimum moisture content, the more pronounced the root reinforcement effect is.…”
Section: Triaxial Shear Test Resultsmentioning
confidence: 99%
“…Adding a root system can/significantly minimize the strainsoftening effect and concurrently increase soil shear strength metrics compared to the absence of a root system (Hallett, 2010;Pollen-Bankhead and Simon, 2010;Park et al, 2021;Su et al, 2021). The closer the sample is to the optimum moisture content, the more pronounced the root reinforcement effect is.…”
Section: Triaxial Shear Test Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that the twisting and strengthening of plant roots in soil can impede the expansion and contraction of the soil [27][28][29][30][31][32]. As a solution for slope protection, green ecological models have been utilized in engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…At the hillslope scale, the presence of vegetation generally increases soil thickness, lowering the frequency of landslide events [10]. Tree roots are regarded as a factor determining the stability of hillsides and riverbanks and can prevent the direct inflow of rainfall on the slope's surface, thus providing stability against surface layer loss and scouring [11] and delaying the process of erosion and massive waste [12][13][14]. Plant roots can enhance slope stability [15][16][17], and their effects are exerted through basal root reinforcement and lateral root reinforcement [18].…”
Section: Introductionmentioning
confidence: 99%